The annals of Chile - Muldoon, Paul 1951- (Farrar, Straus, Giroux, 1994)
The Annals of Chile, Paul Muldoon's first book of new poetry since the acclaimed Madoc: A Mystery (1991), confirms the widely held view that he is the most talented poet of his generation. The heart of the book is the long poem "Yarrow", in which all Muldoon's powers of insight and wordplay and surprising association are on exuberant display. Evoking the 1960s, the poet conjures up a boundless historical present peopled at once by Davy Crockett and Tristan Tzara and Wild Bill Hickok, by Maud Gonne and Michael Jackson, all brought swiftly and vividly to life by his fantastical imagination. The book also contains a group of shorter poems, including "The Birth", a delicate lyric which celebrates the arrival of a baby daughter; "Incantata", a powerful elegy to a former lover; and Muldoon's inspired adaptation of an episode from Ovid's Metamorphoses. Art, Muldoon writes, "builds from pain, from misery, from a deep-seated hurt / a monument to the human heart"; and here, out of strong emotion, in memorable language, Muldoon has once again fashioned rich and vital poetry.
Keywords: Poetry